Decadal Patterns of Forest and Pollinator Recovery Following the Eradication of an Invasive Shrub - Ulyshen, Michael D.; Horn, Scott; Hanula, James L. (Frontiers in Ecology and Evolution, 2022)
Invasive non-native woody shrubs pose a major threat to forested ecosystems in many parts of the world and there is an urgent need for research on the restoration and recovery of these areas. We studied patterns of tree growth and regeneration thirteen years after the experimental eradication (by chainsaw or mulching machine followed by herbicide treatments) of Ligustrum sinense Lour. (Chinese privet) from riparian forests in Georgia, USA. We also followed the recovery of bee and butterfly populations using sites with no history of privet invasion as a reference. By the end of the study, the basal area of restored plots was 24% greater, on average, than still-invaded control plots. Because tree growth rates did not differ among treatments, this increase is attributable to the 60% increase in the number of regenerating native stems (dominated by Acer negundo L.) following privet removal. The benefits of privet removal on pollinators were immediate and long-lasting with the richness and abundance of bees and butterflies being consistently higher in restored plots than in control plots. The diversity, abundance, and composition of bees in restored and reference (i.e., never invaded) plots were comparable by the end of the study. This was less true for butterflies, however, possibly due to the legacy effects of privet invasion on plant communities. Our results demonstrate the long-term benefits of removing privet on forest regeneration and pollinator communities. Indeed, without such efforts, it is probable that forest cover will gradually thin and ultimately disappear from privet-invaded areas as overstory trees die without replacement.